Fenomena Nikah Siri Studi Kasus Desa Kaduhejo Pandeglang - Muhammad Jamiullail Abdulloh; Maulana Ramdani; Rizki Amalia; Niswatin Hadirotul Qudsiyah; Muhammad Wildan Razka Rahtama; Mohamad Rafi Padilah; Eva Fadhilah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The practice of unregistered religious marriage (nikah siri) continues to persist in several rural communities in Indonesia, including Kaduhejo Subdistrict, Pandeglang Regency, where strong religious values intersect with economic and social constraints. Although considered valid according to Islamic law, nikah siri is not formally recorded by the state, resulting in significant legal and social consequences, particularly for women and children. Based on a qualitative normative-empirical approach, this research explores the forms, underlying factors, community perceptions, and socio-legal impacts of nikah siri through in-depth interviews, field observations, and document analysis involving married couples, religious leaders, community figures, and local officials. The findings indicate that economic limitations, socio-cultural traditions, and limited legal awareness are dominant factors sustaining the practice. Most community members prioritize religious legitimacy over administrative legality, while simultaneously acknowledging the legal vulnerabilities arising from unregistered marriages. Nikah siri creates a social dilemma by positioning religious norms, local traditions, and state law in a state of tension rather than harmony. Women and children are the most affected parties, facing legal uncertainty regarding inheritance rights, marital status, and civil documentation. This study offers an empirical contribution by framing nikah siri as a living legal phenomenon shaped by continuous negotiation between normative religious values and structural legal limitations. Strengthening legal education, improving access to marriage registration, and enhancing the economic capacity of young couples are essential strategies to reduce the negative impacts of unregistered marriages in rural communities.